(untitled) (Fiep Bulletin - online, 2019)
Epidemiological, descriptive, retrospective study of the profile of tuberculosis cases in penitentiaries in the state ofParaná, from the years 2012 to 2014. The data come from the Information System of Notification Diseases of Paraná (Sinan). 110inmates diagnosed with tuberculosis were identified in this period, 93.64% of them were male, the highest percentage hadincomplete elementary education II (32.72%). Investigating comorbidities, alcoholism and AIDS were highlighted, both with morecases in those above 35 years of age. It is noteworthy that of the total cases, 87 were new cases and 9 relapses. When crossingdata on comorbidities and schooling, it was observed that the largest number of people affected by AIDS, alcoholism anddiabetes had incomplete Elementary School I. Different studies involving inmates corroborated this research, reiterating that theprofile of this population is similar, emphasizing the need to discuss public policies for health care, especially infectious diseases,such as tuberculosis among persons deprived of their liberty.